Cur Deus Homo vs Homo Deus and the Evolution of Humanity: Quo Vadis? - P. Langerman (Acta Theologica)
This article deals with the profound shifts that are taking place in light of the Fourth Industrial Revolution, in which humanity’s future is highly topical. The article engages Thomas Merton’s re-evaluation of Anselm’s Cur Homo Deo with Harari’s book Homo Deus (2015) and argues that, while we must take Harari’s views seriously, thefuture evolution of humanity is not the human godsuggested by Harari, but that suggested by Merton, who argues that the incarnation shows God’s love for creation; shows Christ as the pattern of what it means to live a holy life, and, ultimately, shows the future of both the cosmos and humanity, where all is taken into the very heart of God. Harari views the future as the creation of a benevolent human god; Merton views the future as a place where all of creation is divinised.